THE EFFECTS OF THE ADDITION OF LYOPHILIZED BERRY FRUITS ON THE LEAVENING PROPERTIES OF DOUGH AND VOLUME PROPERTIES OF BREAD - Kolesárová, Anna (Food and Feed Research, 2024)
This study examined the effects of addition of pulverized lyophilized fruits (chokeberries, black elderberries, blackcurrants, Saskatoon berries) mixed with wheat flour (in amounts of 5%, 10% and 15%) on the quality of dough and bread made from this mixed flour. A reofermetometer F4 was used to evaluate the fermentation of the experimental doughs and a Volscan was used to evaluate the volume of the experimental bread. The dough with 15% addition of black elderberries had the best ability to form fermentation gases, and the dough with 15% addition of Saskatoon berry had the lowest. Doughs supplemented with chokeberry and blackcurrant produced a significantly increased total volume of CO2, but also lost a significant amount of gas during fermentation. The best bread volumes were achieved with the application of elderberry in all investigated amounts, and with the addition of Saskatoon berries in amounts of 5% and 10%. The sensory analysis showed that breads with 5% and 10% fruit additions had the best overall appearance, colour, and textural properties. In the evaluation of the taste properties, breads with the addition of chokeberry, elderberry and Saskatoon berry in the amount of 5% were rated the best.
Keywords: rheofermentometer; gas retention; loaf volume; fruits powder; sensory evaluation; dough rheology